2013
DOI: 10.1002/imhj.21422
|View full text |Cite
|
Sign up to set email alerts
|

Toddler Socioemotional Behavior in a Northern Plains Indian Tribe: Associations With Maternal Psychosocial Well-Being

Abstract: M.C. Sarche, C.D. Croy, C. Big Crow, C. Mitchell, and P. Spicer (2009) provided first-ever information relating the socioemotional development of American Indian toddlers to the immediate context of their mothers' lives. The current study sought to replicate and build on their earlier work by examining the impact of additional maternal risk factors, identified in previous research with non-American Indian populations, on the development of American Indian toddlers: maternal depression, negative social influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…In addition to early cognitive and academic skill development, studies have looked at AIAN children's early socioemotional development (Frankel et al., ; Sarche, Croy, Crow, Mitchell, & Spicer, ). Both Sarche et al.…”
Section: Early Childhood Indicators Among Aian Boys Birth To 8 Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to early cognitive and academic skill development, studies have looked at AIAN children's early socioemotional development (Frankel et al., ; Sarche, Croy, Crow, Mitchell, & Spicer, ). Both Sarche et al.…”
Section: Early Childhood Indicators Among Aian Boys Birth To 8 Yearsmentioning
confidence: 99%
“…() and Frankel et al. () found that a larger percentage of young AIAN children (ages 12–36 months) were rated in the “of concern” range on the externalizing and competence domains of the Infant Toddler Social Emotional Assessment compared to the normative sample (ITSEA; Carter & Briggs‐Gowan, ). Between 14.1% (Frankel et al.)…”
Section: Early Childhood Indicators Among Aian Boys Birth To 8 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests AIAN children struggle to meet reading and math proficiency standards during formal schooling (Moran et al, 2008;National Center for Education Statistics, 2016;Perie, Grigg, & Donahue, 2005), and report higher rates of school absences, dropping out, and identification in special education than other students (DeVoe, Darling-Churchill & Snyder, 2008;Hibel et al, 2008;National Center for Education Statistics, 2016). These educational and wellbeing disparities are manifested as early as kindergarten entry (Frankel et al, 2014;Marks & Garcia Coll, 2007;Mitchell et al, 2011;Sarche et al, 2009) and often persist into adulthood. For instance, AIAN adults are more likely to exhibit problem drinking behaviors, commit suicide, become teen parents and experience negative labor market outcomes such as unemployment and reduced labor force participation rates (Espey et al, 2014;National vital statistics, 2003;Ogunwole, 2006;Olson & Wahab, 2006).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Considera-se que tais eventos adversos podem afetar as famílias tanto a nível intra-sistêmico, quanto em nível inter-sistêmico, exigindo delas, necessidades de ajuste e manutenção do equilíbrio, como proposto por Volling et al (2009). Tal dado corrobora outros estudos que ressaltaram que a exposição recorrente à depressão parental aumentou os riscos do aparecimento de sintomas depressivos nos filhos (Mikkonen et al, 2016), que os sintomas melancólicos das mães mostraram-se associados à depressão infantil (Shannon et al, 2007), que a depressão materna, por si só, caracterizou-se como preditora do surgimento de transtornos de depressão e ansiedade dos filhos (Pilowsky et al, 2006), além de se mostrar associada a mais problemas de internalização, disfunções na regulação das emoções e das competências socioemocionais, como relatado no estudo realizado por Frankel et al (2014).…”
Section: Aspectos Sociodemográfico E Clínico Da Amostra Estudadaunclassified